2012
DOI: 10.3386/w18398
|View full text |Cite
|
Sign up to set email alerts
|

Bubbles, Financial Crises, and Systemic Risk

Abstract: This chapter surveys the literature on bubbles, financial crises, and systemic risk. The first part of the chapter provides a brief historical account of bubbles and financial crisis. The second part of the chapter gives a structured overview of the literature on financial bubbles. The third part of the chapter discusses the literatures on financial crises and systemic risk, with particular emphasis on amplification and propagation mechanisms during financial crises, and the measurement of systemic risk. Final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(120 citation statements)
references
References 11 publications
3
113
0
4
Order By: Relevance
“…These are regimes where investors are herding, following the flock and pushing the price up along an unsustainable growth trajectory. Many other mechanisms have been studied to explain the occurrence of financial bubbles, such as constraints on short selling and lack of synchronisation of arbitrageurs due to heterogeneous beliefs on the existence of a bubble, see Brunnermeier and Oehmke (2012) and Xiong (2013) for two excellent reviews.…”
Section: Phenomenology Of Financial Bubbles and Crashesmentioning
confidence: 99%
“…These are regimes where investors are herding, following the flock and pushing the price up along an unsustainable growth trajectory. Many other mechanisms have been studied to explain the occurrence of financial bubbles, such as constraints on short selling and lack of synchronisation of arbitrageurs due to heterogeneous beliefs on the existence of a bubble, see Brunnermeier and Oehmke (2012) and Xiong (2013) for two excellent reviews.…”
Section: Phenomenology Of Financial Bubbles and Crashesmentioning
confidence: 99%
“…The earlier development of bubbles in distant contracts can be considered as a price-disconnect between spot and futures markets. Although our theory points to rational bubbles as a possible explanation, we remain agnostic as to the cause and note that such bubbles could be underpinned by information frictions, differences of opinion, limits to arbitrage, excess speculation, or time-varying discount factors (see Brunnermeier and Oehmke, 2012;Singleton, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…In their recent survey of the literature on bubbles, Brunnermeier and Oehmke (2013) concluded that "identifying bubbles in the data is a challenging task. The reason is that in FIGURE A.1.-U.K. sample-distribution of 700+ year leaseholds.…”
Section: A2 Existing Time-series Tests Of Rational Bubblesmentioning
confidence: 99%